Two-step numerical procedure on the removal process of gaseous potassium chloride generated from waste incineration via the injection of sulfate-based additives. (15th April 2020) - Kim, Sangwoo; Kim, Beomjong; Lee, Uendo; Hwang, Jungho
Highlights: A two-step numerical procedure to predict the KCl sulfation is proposed. The change in the concentrations of major species with temperature is discussed. The optimal injection temperature for each additive is suggested. The stoichiometric KCl removal efficiency is empirically derived. Abstract: Gaseous potassium chloride ( K C l ) that constitutes a relatively large portion of the combustion gas of municipal solid waste can condense on the surface of boiler heat exchanger tubes, causing severe corrosion attacks. To reduce the chlorine-induced high-temperature corrosion, sulfate-based additives have been used. In this study, a two-step numerical procedure is proposed to quickly predict the effect of the injection of sulfate-based additives on the removal of gaseous K C l . A computational fluid dynamics (CFD) simulation is first carried out to obtain the temperature distribution. Then, the thermal decomposition of sulfate additives, sulfation of gaseous K C l, and condensation of K 2 S O 4 are calculated to predict the species concentration profiles at the temperature conditions given by the CFD simulation. After validation with a laboratory-scale experiment using N H 4 2 S O 4, the procedure is applied to a pilot-scale boiler to examine the effects of N H 4 2 S O 4, F e 2 S O 4 3, and A l 2 S O 4 3 . The calculation results show that each additive has an optimal injection temperature range: approximately 800 °C for N H 4 2 S O 4 and 1000 °C for both F e 2 S O 4 3 and A l 2 S O 4 3, which are consistent with the values reported in the literature. The expressions for the stoichiometric K C l removal efficiency of each additive are derived and compared with the calculated efficiencies.